Identification of Epichloë endophytes associated with wild barley (Hordeum brevisubulatum) and characterisation of their alkaloid biosynthesis. Issue 2 (3rd April 2019) - Chen, Taixiang; Simpson, Wayne R.; Song, Qiuyan; Chen, Shuihong; Li, Chunjie; Ahmad, Rana Z.
ABSTRACT: Epichloë species are biotrophic symbionts of many cool-season grasses that can cause grazing animal toxicosis. We identified fungi from Hordeum brevisubulatum as Epichloë bromicola based on morphological characteristics and tefA and actG gene sequences. Three isolates were examined, they contained perA gene and 10 out of the 14 EAS cluster genes, previously identified in Epichloë inebrians E818. Five out of 11 LTM / IDT cluster genes previously identified in Epichloë festucae Fl1 were present, but no idtG, indicating an inability to produce even early intermediates in the lolitrem B pathway. Only one lolC gene out of 11 LOL cluster genes previously identified in E. festucae E2368 was present in the three isolates. Chemotype analyses revealed infected samples contained only peramine, and not ergine, ergonovine, ergovaline or lolitrem B. This study provides new information about the host range and phylogenetic deﬁnition of E. bromicola and reveal a novel endophyte–grass combination in China.